Pengaruh Usaha Mikro Terhadap Pertumbuhan Ekonomi Kecamatan Girian Kota Bitung - Devie Lumentut (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Micro business activities fields that can develop and are consistent in the national economy. Micro, are a good place for the creation of jobs planned by the government, private sector and individual business actors. As for the purpose of this study is to determine the growth and correlation of micro businesses affect the economic growth of Girian Vilagge, Biyung City. In this study using quantitative methods, namely analyzing and interpreting relationships between variables through accurate data and the latest in accordance with the problems in the study this by using simple linear regression analysis. The results of the study show that the growth variable of Micro Business (X) has a significant value of 1.97 and the relationship of X and Y can be seen from the value of the Pearson correlation that is equal to 0.690 if we see from the guidelines the degree of Pearson correlation is located in section number 4 namely if the value Pearson correlation 0.61 to 0.80 means the level of relationship between variable X and variable Y is strong correlation.